On photokinetics under monochromatic light - Maafi, Mounir (Frontiers in Chemistry, 2023)
The properties of photokinetics under monochromatic light have not yet been fully described in the literature. Also, explicit, handy model equations able to map out the kinetic behaviour of photoreactions have been lacking, for the last 120 years or so. These gaps in the knowledge are addressed in the present paper. Several general features of such photokinetics were investigated, including the effects of initial reactant concentration, the presence of spectator molecules, and radiation intensity. A unique equation, standing for a pseudo-integrated rate-law, capable of outlining the kinetic behaviour of any photoreaction is proposed. Also, a method that solves for quantum yields and absorption coefficients of all species of a given photoreaction is detailed. A metric (the initial velocity) has been adopted and its reliability for quantification of several effects was proven by theoretical derivation, Runge-Kutta numerical integration calculations, and through the model equation proposed. Overall, this study shows that, under monochromatic light, photoreaction kinetics is welldescribed by Φ-order kinetics, that is embodied by a unifying model equation. The paper is aimed at contributing to rationalising photokinetics via reliable, easy-to-use mathematical tools.